Etude Analytique d’un Probleme Quasistatique en Mecanique des Milieux Continues - واني سندس / قدور منى (university of eloued جامعة الوادي, 2024)
هدف هذه المذكرة هو الدراسة النظرية لحركة جسم لزج حراري مع التلف وأساس المذكرة مكونة من فصلين تطرقنا في الفصل الأول الى بعض الوسائل الرياضية اللازمة في هذه المذكرة اما الفصل الثاني مكون من ثلاث أجزاء الجزء الأول نعتبر فيه المشكل الرياضي لهذه الدراسة ويرمز له بالرمز P.ثم باستعمال شكل قرين في الجزء الثاني نحصل على شكل مختلط للمسألة P ويرمز له بالرمز PV .وفي الجزء الثالث والأخير قمنا بدراسة وجود ووحدانية الحل الضعيف للمسألة المطروحة This memory contains a theoretical study of quasistatic contact with friction and normal compliance between a thermo-viscoplastic body with damage and a foundation. This study is composed of two chapters. The first chapter considers the mathematical formulation of the contact problem and analysis recall. The second chapter is divided into three sections. In the first section, we consider the mathematical form of the problem denoted by P, by using the Green form we also obtain a variational form PV, in the second section. Finally, in the third section, we study the existence and uniqueness of a weak solution of the problem
مدكرة ماستررياضيات
Keywords: مواد لدائن عملية شبه ساكنة اتصال احتكاكي نقطة ثابتة; Elastic-viscoplastic materials: Quasistatic process: Frictional contact: Fixed point.